Qumran, Unchecked Parallelomania, and Pseudonymity in Academic Publication - Mizzi, Dennis (Journal of Hellenistic Pottery and Material Culture, 2019)
This monograph has a promising premise – which is to situate Qumran and the Dead Sea Scrolls within the socio-political and cultural milieu of the Graeco-Roman world – but a deeply flawed execution. Its many problems can be summed up into four main points: 1) methodological and interpretative shortcomings; 2) unchecked parallelomania; 3) factual errors; and 4) the use of pseudonymity in academic publication. In the following pages, I will explore each of these issues in some detail. But first, I start with a brief overview of Kenneth Silver’s main arguments and hypothesis.